Tert promotes cardiac regenerative repair after MI through alleviating ROS-induced DNA damage response in cardiomyocyte - Xiaomin Wei; Yilin Zhou; Enge Shao; Xiaoran Shi; Yuan Han; Yeshen Zhang; Guoquan Wei; Hao Zheng; Senlin Huang; Yanmei Chen; Jie Sun; Yulin Liao; et al. (Cell Death Discovery, 2024)
Abstract Telomerase reverse transcriptase (Tert) has been found to have a protective effect on telomeric DNA, but whether it could improve the repair of reactive oxygen species (ROS)-induced DNA damage and promote myocardial regenerative repair after myocardial infarction (MI) by protecting telomeric DNA is unclear. The immunofluorescence staining with TEL-CY3 and the TeloTAGGG Telomerase PCR ELISA kit were used to show the telomere length and telomerase activity. The heart-specific Tert-deletion homozygotes were generated by using commercial Cre tool mice and flox heterozygous mice for mating. We measured the telomere length and telomerase activity of mouse cardiomyocytes (CMs) at different days of age, and the results showed that they were negatively correlated with age. Overexpressed Tert could enhance telomerase activity and lengthen telomeres, thereby repairing the DNA damage induced by ROS and promoting CM proliferation in vitro. The in vivo results indicated that enhanced Tert could significantly improve cardiac function and prognosis by alleviating CM DNA damage and promoting angiogenesis post-MI. In terms of mechanism, DNA pulldown assay was used to identify that nuclear ribonucleoprotein A2B1 (hnRNPA2B1) could be an upstream regulator of Tert in CMs. Overexpressed Tert could activate the NF-κB signaling pathway in CMs and bind to the VEGF promoter in the endothelium to increase the VEGF level. Further immunoblotting showed that Tert protected DNA from ROS-induced damage by inhibiting ATM phosphorylation and blocking the Chk1/p53/p21 pathway activation. HnRNPA2B1-activated Tert could repair the ROS-induced telomeric DNA damage to induce the cell cycle re-entry in CMs and enhance the interaction between CMs and endothelium, thus achieving cardiac regenerative repair after MI.